Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Pelanggan Beberapa Generasi Di Kedai Kopi “Simple Group” Surabaya Dan Gresik - I Gede Wiyasa MS (Universitas 45 Surabaya, 2023)
Service quality is a service that focuses on meeting needs and requirements, as well as on timeliness to meet customer expectations. The purpose of this research is to prove that service quality affects customer satisfaction at the